DETERMINAN PEMILIHAN KONTRASEPSI PADA PASANGAN USIA SUBUR SEBAGAI UPAYA MENEKAN BABY BOOMS DI MASA PANDEMIC COVID-19 DI DESA WARU PARUNG BOGOR - Hasanah, Uswatun; Hakim, Amelia Nurul; Annisa, Mega (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2023)
ABSTRACTCouples of childbearing age ranging in age from 20-45 years where the couple (male and female) is mature enough in all matters especially in the reproductive organs are already functioning properly. Contraception is derived from the word "cons" which means to avoid or fight, and conception means the meeting between mature egg (woman) and sperm cell (male) that causes pregnancy. The purpose of this study is to identify "Factors Influencing The Selection of Contraceptives In Couples of Childbearing Age In An Effort to Suppress Baby Booms During the Covid-19 Pandemic". Research methods use descriptive analytical methods to determine if there is a relationship between independent variables and dependent variables. Cross-sectional design is a type of research in which data related to dependent variables or free variables (independent), data collected by means of questionnaires. The number of samples as many as 55 respondents in Waru Rt Village 03 Rw 06 Parung Bogor in 2021. The results of the study found that there is a relationship between the age of PUS and the selection of contraception (p-value = 0.015), there is a relationship between pus education and the selection of contraception (p-value = 0.032), there is no relationship between pus work and contraceptive selection (p-value = 0.0 08), there is no relationship between pus knowledge and contraceptive selection (p-value = 0.019), and there is no relationship between husband support and contraceptive selection (p-value = 0.032) in Waru Rt Village 03 Rw 06 Parung Bogor.ABSTRAKPasangan usia subur berkisar usia 20-45 tahun dimana pasangan (laki-laki dan perempuan) sudah cukup matang dalam seluruh perihal terlebih pada organ reproduksinya sudah berfungsi dengan baik. Kontrasepsi berasal dari kata “kontra” berarti menghindari ataupun melawan, dan konsepsi berarti pertemuan antara sel telur (wanita) matang dan sel sperma (pria) yang menyebabkan kehamilan. Tujuan penelitian untuk mengidentifikasi faktor-faktor Yang Mempengaruhi Pemilihan Kontrasepsi Pada Pasangan Usia Subur Sebagai Upaya Menekan Baby Booms Di Masa Pandemic Covid-19”. Metode penelitian menggunakan Metode deskriptif analitik.Hasil penelitian didapatkan bahwa ada hubungan antara usia PUS dengan pemilihan kontrasepsi (p-value = 0,015), ada hubungan antara pendidikan PUS dengan pemilihan kontrasepsi (p-value = 0,032), tidak ada hubungan antara pekerjaan PUS dengan pemilihan kontrasepsi (p-value = 0,008), tidak ada hubungan antara pengetahuan PUS dengan pemilihan kontrasepsi (p-value = 0,019), dan tidak ada hubungan antara dukungan suami dengan pemilihan kontrasepsi (p-value = 0,032) di Desa Waru Rt 03 Rw 06 Parung Bogor.